2022
DOI: 10.1093/tas/txac053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a multicomponent microbial feed additive containing prebiotics and probiotics on health, immune status, metabolism, and performance of newly weaned beef steers during a 35-d receiving period

Abstract: We examined the effects of dietary supplementation of a multi-component blend of prebiotics and probiotics on health, immune status, metabolism, and performance of newly weaned beef steers during a 35-d receiving period. Eighty newly weaned crossbred steers (12-hour post-weaning; 206 ± 12 kg of BW) from a single source were stratified by BW into 4 pens (20 steers per pen) such that each pen had similar BW at the beginning of the experiment. The pens were randomly assigned to receive a corn silage-based diet wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Enterococcus and Lactobacillus play key roles in immune function by downregulating the expression of proinflammatory genes and upregulating that of anti-inflammatory genes in the feed of beef steers fed supplemental fermentation products of S. cerevisiae , E. lactis , B. licheniformis , and B. subtilis [ 65 ]. Moreover, Enterococcus and Lactobacillus reportedly improve proteolysis, increase the synthesis of aromatic compounds, and degrade carbohydrates, enhancing the taste and flavor of fermented feed [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enterococcus and Lactobacillus play key roles in immune function by downregulating the expression of proinflammatory genes and upregulating that of anti-inflammatory genes in the feed of beef steers fed supplemental fermentation products of S. cerevisiae , E. lactis , B. licheniformis , and B. subtilis [ 65 ]. Moreover, Enterococcus and Lactobacillus reportedly improve proteolysis, increase the synthesis of aromatic compounds, and degrade carbohydrates, enhancing the taste and flavor of fermented feed [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Description of the RT2 Profiler PCR Array has been published in our previous study [ 26 ]. The real-time PCR analysis was carried out on a QuantStudio 5 Block Real-Time PCR System (Applied Biosystems, Foster City, CA) using the following cycling conditions: 95 °C for 10 min, 40 cycles of denaturation at 95 °C for 15 s and 60 °C 1 min [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Idowu et al. ( 21 ) reported a protective effect of supplemental feed additives containing B. licheniformis against LPS-induced inflammatory stress or tissue damage in new-weaned beef cattle. However, to our knowledge, there is no comprehensive study of B. licheniformis on growth performance, metabolomics, and intestinal health in pigs in an LPS-challenged model.…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al (20) found that both B. licheniformis and Bacillus subtilis (B. subtilis) could promote intestinal growth, improve digestive enzyme activities, and alleviate LPS-induced injury in rats. Idowu et al (21) reported a protective effect of supplemental feed additives containing B. licheniformis against LPS-induced inflammatory stress or tissue damage in new-weaned beef cattle. However, to our knowledge, there is no comprehensive study of B. licheniformis on growth performance, metabolomics, and intestinal health in pigs in an LPS-challenged model.…”
Section: Introductionmentioning
confidence: 99%